(untitled) (Journal of Advances and Scholarly Researches in Allied Education, 2024)
The most often used theme among scholars, politicians, and educated citizens is "Emerging India," which influences many different types of discussions. Expert evaluations and popular commentary are both captivated by India’s seemingly inevitable but delayed rise to global power status. This essay aims to deliver a partial depiction of the forthcoming “challenges and threats” that the foreign policy of India will inevitably face in the coming decades. It begins by examining how foreign policy of New Delhi has changed since gaining independence and how those changes have affected its substance and direction. Subsequently, it addresses the difficulties that modern foreign policy has encountered. Discussed in section III is the danger that China represents regionally and globally. This study also investigates if it is possible for practitioners of Indian foreign policy to adopt a paradigm shift from hard to soft power.